Finite-control-set model predictive control of modular multilevel converters with cascaded open-circuit fault ride-through - Zhou, Dehong (2022)
Open-circuit fault ride-through (FRT) is indispensable for the reliable operation of modular multilevel converters (MMCs). In this paper, finite-control-set model predictive control (FCS-MPC)-based fault detection and isolation (FDI) and fault-tolerant (FT) schemes are proposed for cascaded open-circuit FRT of MMCs. Taking advantage of the known switching state in FCS-MPC, the errors between the applied and estimated inserted submodule (SM) numbers are utilized for FDI directly. These fault diagnostic signals are independent of the voltage and current ratings and not sensitive to parameter variations. Moreover, it can locate the fault very fast within a fundamental period. By introducing the healthy state set of the SMs, an FCS-MPC strategy with cascaded open-circuit FRT is developed. Switching combinations, which will insert the faulty SMs, are inherently avoided by imposing an additional constraint in the cost function. This integrates the FRT into the control scheme, thereby, resulting in seamless FT operations. The reliability improvement by the proposed FRT scheme is numerically analyzed to present the effectiveness of the proposed method. Experimental results show that open-circuit faults can be detected and isolated within several milliseconds and the cascaded open-circuit faults of MMCs can be seamlessly ridden through by the proposed scheme.